Answer:
Step-by-step explanation:
Here, we want to complete the remainder of the table for the given function rule
What this means is that we need to fill in the given y values
To do this, we simply substitute the x values at each point, to get the corresponding y-value
We proceed as follows:
A) At this point , x is-3 , so we substitute -3 for x
Mathematically:
![\begin{gathered} y\text{ = -}((-3))/(3)\text{ + 2} \\ y\text{ = }(3)/(3)\text{ + 2} \\ \\ y\text{ = 1 + 2} \\ y\text{ = 3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u73qoi00w0wplu6o191ylshudodosek2mf.png)
B) Here, x is 0
![\begin{gathered} y\text{ = -}(0)/(3)\text{ + 2} \\ y\text{ = 0 + 2} \\ y\text{ = 2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/meayrj7flbpb7it7nxl6hy15h12rr3nmmt.png)
C) Here, x is 3
![\begin{gathered} y\text{ = -}(3)/(3)\text{ + 2} \\ y\text{ = -1 + 2} \\ y\text{ = 1} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/72i2m29s5yjyiivd8z51dcc8be4clmkod8.png)
D) Here, x is 6
![\begin{gathered} y\text{ = -}(6)/(3)\text{ + 2} \\ y\text{ = -2 + 2} \\ y\text{ = 0} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yrm8kti3b50vhasyzq93qzimgfmh3s4tbj.png)